2012
DOI: 10.1068/p7244
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Perception is Positively Linked to Anxiety in Young Adults

Abstract: Abstract. Olfactory abilities show a high degree of inter-individual variability and this could be partly related to personality differences. Here, in two studies, we tested a potential link between personality dimensions and olfactory perception. Sixty-eight (study 1) and a hundred and fifty-six (study 2) young adults completed the Big Five questionnaire and performed the Sniffin' Sticks test for assessing odour threshold, identification, and (in study 2) discrimination. In neither study did we find a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…In contrast, another study by Herberner et al (1989) demonstrated that, in comparison to extremely sociable participants, extremely shy participants were significantly more sensitive to odors. Furthermore, several studies reported no significant relationship between olfactory sensitivity and extraversion/introversion (Filsinger et al, 1987; Koelega, 1994; Pause et al, 1998; Larsson et al, 2000; Havlíček et al, 2012). Pause et al (1998) found that neuroticism, when compared to extraversion, has a stronger impact in determination of olfactory sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, another study by Herberner et al (1989) demonstrated that, in comparison to extremely sociable participants, extremely shy participants were significantly more sensitive to odors. Furthermore, several studies reported no significant relationship between olfactory sensitivity and extraversion/introversion (Filsinger et al, 1987; Koelega, 1994; Pause et al, 1998; Larsson et al, 2000; Havlíček et al, 2012). Pause et al (1998) found that neuroticism, when compared to extraversion, has a stronger impact in determination of olfactory sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Personality is another potential factor in modulating olfactory perception (Koelega, 1970, 1994; Filsinger et al, 1987; Pause et al, 1998; Larsson et al, 2000; Chen and Dalton, 2005; Havlíček et al, 2012;; La Buissonnière-Ariza et al, 2013). Earlier research demonstrated plausible relationships between olfactory sensitivity and personality traits such as extraversion/introversion; the results, however, are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Since this study was part of a broader project, including a study by Havlíček and colleagues [35] on the relation of Big Five personality traits and olfactory abilities, the participants further completed several other questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…[68] Indeed, nine of 16 target smells in the Odor Identification Test represent a smell from foods or beverages. A higher level of anxiety is significantly associated with enhanced odor identification in individuals without AN,[22,69] and anxiety is associated with a tendency to attend to threatening information. [70] Superior odor identification in individuals with AN may therefore represent an attentional bias toward feared stimuli related to eating.…”
Section: Discussionmentioning
confidence: 99%